Asphaltene deposition control by chemical inhibitors : theoretical and practical prospects /: theoretical and practical prospects. (2021) - Ghamartale, Ali; Afzali, Shokufe; Rezaei, Nima; Zendehboudi, Sohrab
No abstract available